The macrophage-associated microRNA-4715-3p / Gasdermin D axis potentially indicates fibrosis progression in nonalcoholic fatty liver disease: evidence from transcriptome and biological data. Issue 5 (2nd May 2022) - Chen, Shuai; Cai, Xiurong; Liu, Yu; Shen, Yu; Guillot, Adrien; Tacke, Frank; Tang, Liming; Liu, Hanyang
ABSTRACT: Nonalcoholic fatty liver disease (NAFLD) is highly possible to progress to cirrhosis, malignancy, and liver failure through fibrogenesis. The enormous potential of pathogenetic and therapeutic targets in NAFLD has been revealed. This study aimed to explore novel factors potentially indicating or mediating NAFLD progression. Multiple bulk and single-cell RNA sequencing datasets were used, in which landscapes of cell populations were clarified to characterize immune cell infiltration. Significantly high infiltration of macrophages (MPs) was discovered during NAFLD progression. Samples in bulk NASH datasets were regrouped by MP level. Highly differentially expressed genes (DEGs) were identified in the Ctrl vs. NASH comparison, low MP vs. high MP comparison, and the weighted gene co-expression network analysis (WGCNA) clusters. Eight hub genes were identified as promising targets by protein–protein interaction analysis and validated in fibrosis progression, microRNA (miR)–protein interactions were predicted, and the hub genes were verified in a free fatty acid (FFA)-induced macrophage injury model. The results showed that Gasdermin D ( GSDMD ) was upregulated with fibrosis progression in NAFLD and was associated with macrophage infiltration. In addition, a potential regulator (miR-4715-3p) was correlated with GSDMD . The miR-4715-3p/ GSDMD axis potentially modulates macrophage-associated immunity and indicates fibrosis progression in NAFLD. Graphical Abstract: uf0001